Pengaruh Green Banking Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening - Maulana, Moch. Ganjar; Muzayyanah; Indriyani, Rinni; Sari, Fitriya (Akmenika: Jurnal Akuntansi dan Manajemen, 2025)
This study examines the effect of the implementation of Green Banking on company value with profitability as a mediating variable in IKBI member banks in 2022. The background of this research is motivated by the strategic role of the banking sector in supporting economic growth and environmental sustainability. Secondary data was taken from the financial statements of 15 IKBI member banks during the 2019–2022 period. The analysis was carried out by multiple linear regression and path analysis to test the relationship between Green Banking, profitability (measured by ROA), and company value (measured by PBV). The results of the study show that Green Banking activities have a significant positive effect on profitability and company value. The increase in green activities at banks contributes to the increase in ROA, which further increases the value of the company directly or indirectly. These findings support a signal theory that transparency in sustainability implementation can.